Method for synthesizing hydrogen carried by quartz glass

Through the three-stage heat treatment method, the existing hydrogen-carrying process of quartz glass is solved, and the rapid hydrogen-carrying process, excellent refractive index uniformity and UV radiation resistance are achieved.

CN119591329APending Publication Date: 2025-03-11CHANGFEI QUARTZ TECH (WUHAN) CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411770132.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing hydrogen-carrying process of quartz glass takes a long time, and the hydrogen molecular concentration distribution is difficult to control, resulting in poor refractive index uniformity and UV radiation resistance of quartz glass after hydrogen loading.

Method used

Three-stage heat treatment method is adopted: first one heat treatment is performed in a hydrogen atmosphere, then two heat treatment is performed in a vacuum environment, and finally three heat treatment is performed in a hydrogen-containing atmosphere to improve the uniformity of the hydrogen molecular concentration distribution in quartz glass.

Benefits of technology

The hydrogen-carrying time of quartz glass is significantly shortened, the appropriate distribution of hydrogen molecular concentration is achieved, and the refractive index uniformity and UV radiation resistance of synthetic quartz glass are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170059320000041
    Figure BDA0005170059320000041
  • Figure HDA0005170059330000011
    Figure HDA0005170059330000011
  • Figure HDA0005170059330000012
    Figure HDA0005170059330000012
Patent Text Reader

Abstract

The invention belongs to the technical field of quartz glass, and discloses a synthetic quartz glass hydrogen loading method, which comprises: carrying out a first-stage heat treatment on synthetic quartz glass in a hydrogen atmosphere, carrying out a second-stage heat treatment in a vacuum atmosphere, and finally carrying out a third-stage heat treatment in a hydrogen-containing atmosphere so as to obtain the hydrogen-containing synthetic quartz glass. The hydrogen loading method is simple in step, quartz hydrogen loading can be completed within a short time, and the concentration of hydrogen molecules in the synthetic quartz glass meets characteristic distribution, so that the obtained hydrogen-containing synthetic quartz glass has excellent refractive index uniformity and ultraviolet radiation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quartz glass, and in particular relates to a method for synthesizing quartz glass to carry hydrogen. Background Art

[0002] High-purity synthetic quartz glass has become the preferred material for lens elements used in high-resolution deep ultraviolet projection lithography equipment in the semiconductor field. It is well known that the presence of hydrogen molecules in quartz glass is very necessary, which can significantly improve the ability of quartz glass to resist damage from 193nm and 248nm excimer laser irradiation. However, quartz glass prepared by soot process and other methods does not contain hydrogen molecules. Therefore, it is necessary to heat treat in a hydrogen atmosphere to load hydrogen molecules into the quartz glass.

[0003] Domestic semiconductor technology started late, and there is little research on quartz hydrogen loading process. CN113415978A discloses a method for preparing radiation-resistant quartz glass, which carries out hydrogen loading treatment on optical quartz glass under high temperature and high pressure. However, hydrogen loading at too high a temperature will produce a large number of SiH defects in the quartz glass. These SiH defects will reduce the transmittance of quartz glass at 193nm and 248nm under excimer laser irradiation, and the prepared quartz material is not suitable for use in photolithography equipment. Therefore, hydrogen loading is usually completed by diffusing hydrogen molecules in the furnace into the glass at a low temperature below 500°C, and the concentration of hydrogen molecules in the quartz glass is determined by the diffusion rate and diffusion time. Since hydrogen molecules diffuse very slowly at low temperatures, it often takes a lot of time of several months for hydrogen molecules to diffuse into the interior of the quartz glass and reach the required target concentration. Loading hydrogen has become one of the most expensive steps in the manufacture of quartz glass. In addition, the concentration distribution of hydrogen molecules in the quartz glass has a significant effect on the uniformity of the refractive index, and the control of the concentration distribution is also a difficult problem currently faced. Therefore, it is very necessary to seek a quartz hydrogen loading method that can reduce the loading time and achieve a suitable hydrogen molecule concentration distribution. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for hydrogen loading in synthetic quartz glass in view of the shortcomings of the prior art, which can complete the hydrogen loading in quartz in a relatively short time and make the concentration distribution of hydrogen molecules appropriate. The obtained hydrogen-containing synthetic quartz glass has excellent refractive index uniformity and ultraviolet radiation resistance.

[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a method for carrying hydrogen in synthetic quartz glass, comprising the following steps:

[0006] The synthetic quartz glass is firstly subjected to a first-stage heat treatment in a hydrogen atmosphere, then subjected to a second-stage heat treatment in a vacuum environment, and finally subjected to a third-stage heat treatment in a hydrogen-containing atmosphere, thereby obtaining hydrogen-containing synthetic quartz glass.

[0007] In the above solution, the synthetic quartz glass has a metal impurity content of less than 100 ppb and a hydroxyl content of less than 200 ppm.

[0008] In the above solution, the synthetic quartz glass is a cylinder or a right quadrangular prism with a height not exceeding 120 mm.

[0009] In the above scheme, the hydrogen atmosphere pressure of the first stage heat treatment is 0.1-1 MPa, the treatment temperature is 300-500° C., and the treatment time is 50-500 h.

[0010] Preferably, the hydrogen atmosphere pressure of the first stage heat treatment is 0.3-0.8 MPa, the treatment temperature is 400-500° C., and the treatment time is 150-500 h.

[0011] In the above scheme, the vacuum pressure of the second stage heat treatment is ≤20Pa, the treatment temperature is 300-500°C, and the treatment time is 50-500h.

[0012] Preferably, the vacuum pressure of the second-stage heat treatment is ≤10Pa, the treatment temperature is 400-500°C, and the treatment time is 150-500h.

[0013] In the above scheme, the volume fraction of hydrogen in the hydrogen-containing atmosphere of the three-stage heat treatment is 1-25%, and the rest is nitrogen or argon.

[0014] In the above scheme, the hydrogen partial pressure in the hydrogen-containing atmosphere of the three-stage heat treatment is 0.01-0.1 MPa, the treatment temperature is 300-500° C., and the treatment time is 50-500 h.

[0015] Preferably, the hydrogen partial pressure in the hydrogen-containing atmosphere of the three-stage heat treatment is 0.02-0.08 MPa, the treatment temperature is 400-500° C., and the treatment time is 150-500 h.

[0016] In the above scheme, the concentration of hydrogen molecules in the hydrogen-containing synthetic quartz glass is monotonically increasing from the cross section where the midpoint of the central axis is located toward the upper bottom surface and the lower bottom surface respectively.

[0017] In the above scheme, the concentration of hydrogen molecules in the hydrogen-containing synthetic quartz glass is distributed in the range of 2×10 16 Molecules / cm 3 ~3×10 17 Molecules / cm 3 .

[0018] In the above solution, the refractive index uniformity of the hydrogen-containing synthetic quartz glass is ≤1.5ppm.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The existing hydrogen loading method consumes a lot of time and is difficult to control the distribution of hydrogen molecules in synthetic quartz glass, which not only has high production costs, but also has poor uniformity of refractive index of synthetic quartz glass after hydrogen loading, which affects its practical application. The hydrogen loading method of the present invention has simple steps, can complete quartz hydrogen loading in a relatively short time, and makes the concentration of hydrogen molecules in synthetic quartz glass meet the characteristic distribution, so that the obtained hydrogen-containing synthetic quartz glass has excellent refractive index uniformity and ultraviolet radiation resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the structure of hydrogenated synthetic quartz glass in the embodiment and comparative example.

[0022] Figure 2 This is a distribution diagram of hydrogen molecule concentration in hydrogen-containing synthetic quartz glass in Example 1.

[0023] Figure 3 This is the distribution diagram of hydrogen molecule concentration in hydrogen-containing synthetic quartz glass of Comparative Example 1.

[0024] Figure 4 This is the distribution diagram of hydrogen molecule concentration in hydrogen-containing synthetic quartz glass of comparative example 2.

[0025] Figure 5 This is the distribution diagram of hydrogen molecule concentration in hydrogen-containing synthetic quartz glass of comparative example 3.

[0026] Figure 6 This is a distribution diagram of hydrogen molecule concentration in hydrogen-containing synthetic quartz glass of comparative example 4. DETAILED DESCRIPTION

[0027] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0028] Example 1

[0029] Example 1 The synthetic quartz glass prepared by the soot process has a metal impurity content of less than 50 ppb and a hydroxyl content of 100 ppm. It is cylindrical with a bottom diameter of 320 mm and a height of 80 mm.

[0030] Example 1 The above synthetic quartz glass is loaded with hydrogen in the following steps:

[0031] The synthetic quartz glass is first subjected to a heat treatment in a 100% hydrogen atmosphere, the hydrogen atmosphere pressure is 0.5 MPa, the treatment temperature is 475° C., and the treatment time is 400 h;

[0032] Then, a second heat treatment is carried out in a vacuum environment, with a vacuum pressure of ≤10Pa, a treatment temperature of 475°C, and a treatment time of 200h;

[0033] Finally, three stages of heat treatment are carried out in a hydrogen-containing atmosphere, in which the volume fraction of hydrogen is 20% and the rest is nitrogen. The hydrogen partial pressure in the hydrogen-containing atmosphere is 0.025 MPa, the treatment temperature is 475°C, and the treatment time is 400 h.

[0034] Comparative Example 1

[0035] The only difference between Comparative Example 1 and Example 1 is that no vacuum environment heat treatment is performed, and the time of the hydrogen-containing atmosphere heat treatment is adjusted from 400 h to 600 h.

[0036] Comparative Example 2

[0037] The difference between Comparative Example 2 and Example 1 is that the vacuum environment heat treatment and the hydrogen atmosphere heat treatment are not performed, and the time of the 100% hydrogen atmosphere heat treatment is adjusted from 400 hours to 1000 hours.

[0038] Comparative Example 3

[0039] The difference between Comparative Example 3 and Example 1 is that: no 100% hydrogen atmosphere heat treatment and vacuum environment heat treatment are performed, the hydrogen partial pressure of the hydrogen atmosphere heat treatment is maintained at 0.025 MPa, but the time is adjusted from 400 h to 1000 h.

[0040] Comparative Example 4

[0041] The difference between Comparative Example 4 and Example 1 is that: no 100% hydrogen atmosphere heat treatment and vacuum environment heat treatment are performed, the hydrogen partial pressure of the hydrogen atmosphere heat treatment is maintained at 0.025 MPa, but the time is adjusted from 400 h to 6000 h.

[0042] The hydrogen molecule concentration distribution in the hydrogen-containing synthetic quartz glass obtained in Example 1 and Comparative Examples 1 to 4 and the refractive index uniformity of the hydrogen-containing synthetic quartz glass were tested. The refractive index uniformity reflects the distribution of the refractive index and is measured at a wavelength of 633 nm using a ZYGO interferometer equipped with a helium-neon laser. The hydrogen molecule concentration is measured by Raman spectroscopy, using the 4135 cm-1 wavelength in the laser Raman spectrum that represents the fundamental vibration between silicon and oxygen. -1 The intensity of the scattering peak at 4135 With 800 cm -1 The intensity of the scattering peak at 800 The intensity ratio (I 4135 / I 800 ) to obtain the hydrogen molecule concentration (molecules / cm 3 ), the detection limit of this method is 1*10 16 Molecules / cm 3 , below the detection limit means there is no hydrogen molecule and no radiation resistance. The specific test results are shown in Table 1 and Figures 2 to 6 .

[0043] Table 1

[0044]

[0045] The test results show that the concentration of hydrogen molecules in the hydrogen-containing synthetic quartz glass obtained in Example 1 is monotonically increasing from the cross section at the midpoint of the central axis to the upper bottom surface and the lower bottom surface, and the concentration of hydrogen molecules is distributed in the range of 5.1×10 16 Molecules / cm 3 ~2.5×10 17 Molecules / cm 3 , the refractive index uniformity is 1.0ppm, and its original good optical uniformity is maintained, which can be used in the field of semiconductor lithography. The hydrogen molecule concentration distribution in the hydrogen-containing synthetic quartz glass obtained in Comparative Example 1 does not satisfy the monotonically increasing trend, the refractive index uniformity is 1.6ppm, and the optical uniformity is reduced; although the hydrogen molecule concentration distribution in the hydrogen-containing synthetic quartz glass obtained in Comparative Example 2 shows a monotonically increasing trend, the concentration distribution span is too large, the refractive index uniformity is 2.5ppm, and the optical uniformity is significantly reduced; although the hydrogen molecule concentration distribution in the hydrogen-containing synthetic quartz glass obtained in Comparative Example 3 shows a monotonically increasing trend, due to the absence of hydrogen molecules in the central area, it does not have radiation resistance; the hydrogen-containing synthetic quartz glass obtained in the above comparative examples is not suitable for use in the field of semiconductor lithography. The hydrogen molecule concentration distribution and refractive index uniformity of the hydrogen-containing synthetic quartz glass obtained in Comparative Example 4 both meet the requirements of the present invention, but it takes as long as 6000 hours. The applicant conducted a test for 1000 to 6000 hours under the conditions of Comparative Document 4 and found that a technical effect similar to that of the present invention can only be achieved when the processing time reaches 6000 hours, resulting in a sharp increase in production costs.

[0046] Example 2

[0047] Example 2 The synthetic quartz glass prepared by the soot process has a metal impurity content of less than 50 ppb and a hydroxyl content of 80 ppm. It is in the shape of a regular quadrangular prism with a bottom side length of 400 mm and a height of 60 mm.

[0048] Example 2 The above synthetic quartz glass is loaded with hydrogen in the following steps:

[0049] The synthetic quartz glass is first subjected to a heat treatment in a 100% hydrogen atmosphere, the hydrogen atmosphere pressure is 0.4 MPa, the treatment temperature is 450° C., and the treatment time is 250 h;

[0050] Then, a second heat treatment is carried out in a vacuum environment, with a vacuum pressure of ≤10Pa, a treatment temperature of 450°C, and a treatment time of 100h;

[0051] Finally, three stages of heat treatment are carried out in a hydrogen-containing atmosphere, in which the volume fraction of hydrogen is 20% and the rest is nitrogen, the hydrogen partial pressure is 0.035 MPa, the treatment temperature is 450°C, and the treatment time is 250 h.

[0052] After testing, the concentration of hydrogen molecules in the hydrogen-containing synthetic quartz glass obtained in Example 2 is monotonically increasing from the cross section at the midpoint of the central axis to the upper bottom surface and the lower bottom surface, and the concentration of hydrogen molecules is distributed in the range of 4.2×10 16 Molecules / cm 3 ~2.8×10 17 Molecules / cm 3 The refractive index uniformity is 1.1ppm, which maintains its original good optical uniformity and can be used in the field of semiconductor lithography.

[0053] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A method for synthesizing hydrogen in quartz glass, characterized in that: The following steps are involved: The synthetic quartz glass is firstly subjected to a first-stage heat treatment in a hydrogen atmosphere, then subjected to a second-stage heat treatment in a vacuum environment, and finally subjected to a third-stage heat treatment in a hydrogen-containing atmosphere, thereby obtaining hydrogen-containing synthetic quartz glass.

2. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The hydrogen atmosphere pressure of the one-stage heat treatment is 0.1-1 MPa, the treatment temperature is 300-500° C., and the treatment time is 50-500 h.

3. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The vacuum pressure of the second-stage heat treatment is ≤20Pa, the treatment temperature is 300-500°C, and the treatment time is 50-500h.

4. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The hydrogen partial pressure in the hydrogen-containing atmosphere of the three-stage heat treatment is 0.01-0.1 MPa, the treatment temperature is 300-500° C., and the treatment time is 50-500 h.

5. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The hydrogen atmosphere pressure of the first stage heat treatment is 0.3-0.8MPa, the treatment temperature is 400-500°C, and the treatment time is 150-500h; the vacuum pressure of the second stage heat treatment is ≤10Pa, the treatment temperature is 400-500°C, and the treatment time is 150-500h; the hydrogen partial pressure in the hydrogen-containing atmosphere of the third stage heat treatment is 0.02-0.08MPa, the treatment temperature is 400-500°C, and the treatment time is 150-500h.

6. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The volume fraction of hydrogen in the hydrogen-containing atmosphere of the three-stage heat treatment is 1-25%, and the rest is nitrogen or argon.

7. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The concentration of hydrogen molecules in the hydrogen-containing synthetic quartz glass is monotonically increasing from the cross section where the midpoint of the central axis is located toward the upper bottom surface and the lower bottom surface respectively.

8. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The hydrogen molecule concentration in the hydrogen-containing synthetic quartz glass is distributed in the range of 2×10 16 Molecules / cm 3 ~3×10 17 Molecules / cm 3 .

9. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The refractive index uniformity of the hydrogen-containing synthetic quartz glass is ≤1.5ppm.

10. The method for carrying hydrogen in synthetic quartz glass according to claim 1, characterized in that: The synthetic quartz glass has a metal impurity content of less than 100 ppb and a hydroxyl content of less than 200 ppm; the synthetic quartz glass is a cylinder or a right quadrangular prism with a height not exceeding 120 mm.

Citation Information

Cited By

  • Preparation method of deep ultraviolet quartz glass and deep ultraviolet quartz glass

    CN120887638A

  • Method for preparing deep-ultraviolet quartz glass and deep-ultraviolet quartz glass

    CN120887638B

  • Hydrogen-containing synthetic quartz glass, method for producing the same, and use thereof

    CN122748893A